Application of Blended Learning Model to Improve Online Learning Activities for Basic Computer and Networking for Students - Jannah, Miftahul; Nurdin, Enjang Ali; Hardianti, Tati (Jurnal Guru Komputer, 2021)
This study aims to (1) Design and implement Blended Learning model on the subjects of computer assembly for class X TKI at SMKN 2 Bandung. (2) Knowing the difference in outcomes activity learning of students who are using the Blended Learning model and those who do not use the Blended Learning model of learning in the subjects Computer Assembly class X TKI SMK Negeri 2 Bandung (3) Knowing the students' response to the learning model of Blended Learning using Moodle e-learning in the subjects Computer Assembly class X TKI SMK Negeri 2 Bandung. The stage of this study are: (1) Preparation and planning (2) Research (3) Presentation of the study results. The data analysis used t-test to determine differences in learning outcomes, and added with questionnaire to know the responses of the students. The results showed that: (1) The results of the validation study media get a validity of 83.6% with very valid criteria (2) The results of the validation RPP get a validity of 88.5% with very valid criteria (3) The results of the validation items to get the validity of 88.8% with very valid criteria (4) The results of responses of student about learning model of Blended Learning using Moodle e-learning media earned an average rating of 75.3% and is considered good.